INVITRO ANTI - MICROBIAL ACTIVITY OF HERBALFORMULATION (SEETHABEDHI VADAGAM) - Surya, D.; Gandhimathi, S.; Shameem, F. R. (International Journal of Ayurveda and Pharma Research, 2015)
Siddha system of medicine is the most primitive medicinal system, a source for relief from illness. Medicinal plants represent a rich source of antimicrobial agents. The present study was taken to investigate the in vitro-anti microbial activity of herbal drug Seethabedhi vadagam indicated for all types of Dysentery, which is the traditional Siddha polyherbal formulation. In children dysentery is major risk factor for malnutrion and death. Disc diffusion method was used for invitro antibacterial screening, zones of inhibition were observed in disc diffusion for anti-microbial investigation against gram positive and gram negative pathogenic bacteria. Different concentrations of drugs were used to see the antimicrobial activity. The present study revealed that maximum growth of inhibition and effectiveness was remarkably observed in the extracts of Seethabedhi Vadagam. These results indicate that Seethabedhi Vadagam have potential antibacterial activity against E.coli and B.subtilis.